The Process and the Learning of Workplace Devaluation: A Malaysian Case Study - Chin, Yook Kong (2002)
Workers recognized and appreciated overtly by the management perceive themselves as valued employees. In contrast, employees that are not rewarded or not recognized perceive themselves as either un-valued or undervalued. On the other hand, valued employees feel devalued when they are subjected to situations that symbolize that the organization is ignoring their contributions, commitment and competence. This qualitative case study seeks to understand the experiences of six devalued managers of one Malaysian organization. They were transferred to a new post that commands reduced positional power, reduced influence and carries lower job scope and responsibilities when compared to the previous post. Data was collected through a series of in-depth interviews. Findings were extracted through grounded theory analysis techniques of open coding, constant comparison, storyline, memos and diagrams. The findings produced a three-phase process of workplace devaluation. "Agitation," the first phase, was a period of suspense, anxiety, uncertainty and hope for the individuals. "Assimilation," the second phase, was a period of intense internal self-struggle for the individuals. They experienced states of conflict, denial and rationalization. In "Acknowledgment," the third phase, the individuals either passively accept (acknowledge) their situation or act to redress their condition.